Leadership and organizational culture as dual levers of work wthic in local government: Evidence of indirect – only and complementary mediation via job satisfaction at Kecamatan Pasar Rebo, Jakarta - Rahayu, Lidiana Endah Viefrien (Privietlab, 2025)
This study examines how leadership and organizational culture shape civil servants’ work ethic in a Jakarta sub-district office, with job satisfaction specified as a mediating mechanism. Using a cross-sectional survey and hypothesis-testing design, we validated multi-item measures for leadership (supportive, directive, participative, achievement-oriented behaviors), organizational culture (shared values and routines), job satisfaction (pay/benefits, supervision, work content, opportunities), and work ethic (punctuality, diligence, adaptability). Measurement screening indicated satisfactory reliability and item validity. Regression/SEM results show that leadership and organizational culture both positively predict job satisfaction (R² ≈ .43). In the work-ethic model, organizational culture and job satisfaction exhibit positive, significant effects, while the direct leadership effect is non-significant; model fit explains a meaningful share of variance in work ethic (R² ≈ .20). Indirect-effect computations indicate an “indirect-only” mediation for leadership (leadership → satisfaction → work ethic) and “complementary” mediation for culture (direct + indirect paths in the same direction). Substantively, leader behaviors elevate employees’ felt fairness, clarity, and recognition, which translate into ethical diligence, whereas culture both institutionalizes normative expectations that directly pull behavior and simultaneously raises satisfaction. The findings support a dual-track improvement strategy: invest in participative, feedback-rich leadership to lift satisfaction, and codify culture norms (learning from mistakes, fair rewards, teamwork, punctuality) to directly and indirectly strengthen work ethic. Implications include embedding feedback cycles, clarifying performance standards, and aligning recognition/promotion systems with targeted ethical behaviors.